Development and validation of the multidimensional version of the fear of self questionnaire: Corrupted, culpable and malformed feared possible selves in obsessive–compulsive and body‐dysmorphic symptoms. (23rd February 2021) - Aardema, Frederick; Radomsky, Adam S.; Moulding, Richard; Wong, Shiu F.; Bourguignon, Lysandre; Giraldo‐O'Meara, Martha
Abstract: In recent years, cognitive‐behavioural models of OCD have increasingly recognized the potential role of feared possible selves in the development and maintenance of OCD, while simultaneously re‐examining factors that have historically been linked to self‐perceptions in OCD. The current article describes the development and validation of a multidimensional version of the Fear of Self Questionnaire (FSQ‐EV) in a non‐clinical ( N = 626) and clinical OCD sample ( N = 79). Principal component analyses in the non‐clinical sample revealed three conceptually and factorially distinct components revolving around a feared corrupted possible self, a feared culpable possible self and a feared malformed possible self. The questionnaire showed a strong internal inconsistency, and good divergent and convergent validity, including strong relationships to obsessional symptoms. In particular, the corrupted feared self predicted OCD symptoms independently from depression and other related self‐constructs and obsessive beliefs, while also strongly interacting with importance and control of thoughts in the prediction of almost all specific symptoms of OCD. Results are consistent with the notion that self‐constructs can be conceptually and empirically distinguished from obsessive beliefs and appraisals with significant potential to improve our understanding of OCD and related disorders.